ANALYSIS OF THE EFFECTIVENESS OF INTERACTIVE LEARNING METHODS USED BY LECTURERS IN IMPROVING STUDENT ACHIEVEMENT - Rita Hayati; Muhammad Mahfud; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2024)
This study aims to analyse the effectiveness of interactive learning methods applied by lecturers in improving students' academic achievement. Through this study, it was found that the implementation of interactive learning methods had a positive and significant impact on student engagement and achievement. The method, which involves discussion, group work, and multilevel activities, is proven to improve students' understanding of the material and critical thinking skills. The role of the lecturer as a facilitator is crucial in ensuring the effectiveness of this method, with good activity design and clear direction identified as key to success. In addition, physical and social environments that support interaction also contribute positively to a conducive learning atmosphere. In conclusion, interactive learning methods are effective in improving student achievement, provided they are implemented with appropriate strategies and a supportive environment.